2009
DOI: 10.1021/jf9003913
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects and Molecular Mechanism of Dieckol Isolated from Marine Brown Alga on COX-2 and iNOS in Microglial Cells

Abstract: To identify the neuroprotective effect of dieckol, a hexameric compound of phloroglucinol isolated from marine brown alga, Ecklonia cava , this study investigated the anti-inflammatory effect of dieckol on lipopolysaccharide (LPS)-stimulated murine BV2 microglia and elucidated the molecular mechanism. The results showed that dieckol suppresses LPS-induced production of nitric oxide (NO) and prostaglandin E(2) (PGE(2)) and expression of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) in a do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
87
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(97 citation statements)
references
References 29 publications
(36 reference statements)
9
87
1
Order By: Relevance
“…NF-κB is one of the principal factors for the expression of COX-2 and iNOS as mediated by the LPS or pro-inflammatory cytokines [11]. The present study identified that NF-κB is responsible for the maintenance of iNOS expression [9].…”
Section: Effects Of P Thunbergii Extracts On Lps-induced Nuclear Trasupporting
confidence: 51%
“…NF-κB is one of the principal factors for the expression of COX-2 and iNOS as mediated by the LPS or pro-inflammatory cytokines [11]. The present study identified that NF-κB is responsible for the maintenance of iNOS expression [9].…”
Section: Effects Of P Thunbergii Extracts On Lps-induced Nuclear Trasupporting
confidence: 51%
“…conclusion From our finding in addition to little toxicity of phlorotannins and those main components (Nagayama et al, 2002;Jung et al, 2009;Kim et al, 2009;Shim et al, 2009;, we suggest that E. kurome polyphenol (KPP) consumption might be useful to prevent DM-II and diabetes-related complications.…”
Section: Discussionmentioning
confidence: 66%
“…These inhibitory effects may cause a reduction in the synthesis and release of leukotoriene and prostaglandin [34]. Further, dieckol from E. cava was shown as a neuroprotective agent due to alleviation of iNOS and COX-2 expression in BV2 microglia [35]. Similarly, dieckol from E. cava, diphlorethohydroxycarmalol from Ishige okamurae, and phlorofucofuroeckol A from Ecklonia stolonifera also displayed potent down-regulation on iNOS and COX-2 expression in human umbilical vein endothelial cells and RAW 264.7 macrophage cells [36][37][38].…”
Section: Inhibition Of Inflammation-mediating Enzymesmentioning
confidence: 98%